Selective C–C bond cleavage of cycloketoximes via iminyl radicals and distal carbon radicals through photocatalysis - Iram Kalsoom; Muhammad Bilal; Aqsa Kanwal; Nasir Rasool; Usman Nazeer; Codrut Ciurea; Andrea Elena Neculau; Carmen Constantina Martinescu (Journal of Saudi Chemical Society, 2024)
The photocatalyzed cleavage of cycloketoximes is a promising approach for modifying their biological activity and designing prodrugs activated by light. Cycloketoximes containing a cyclic ring structure that can hinder their degradation and modification in biological systems. Photocatalysis offers a sustainable and efficient method for breaking down the cyclic structure using a photocatalyst and exposure to ultraviolet light. These reactions are initiated by iminyl radicals, that gain access to distal-carbon through selective C–C cleavage. This process provides a solution for the challenging task of modifying the biological activities of cycloketoximes. Moreover, it can also be useful for selectively removing protecting groups from organic molecules or cleaving specific chemical bonds, thereby facilitating organic synthesis.This review article covers synthetic uses of photocatalyzed cleavage of cycloketoximes and highlights its ongoing research in the field of photocatalysis.